WORKLOAD DYNAMICS OF MEDICAL PROFESSIONALS IN BULGARIAN HEALTHCARE SYSTEM: EVIDENCES FROM AGGREGATE DATA - Nikolay Atanasov; Krikor Indjian (Journal of IMAB)
Purpose. This study aims to analyze the tendencies of the workload of medical professionals in Bulgaria after the liberal reforms in the national healthcare system. Material/Methods. Basic econometric methods, such as tests for structural breaks and dynamic rows modeling based on "macro-" or aggregate data, are implemented. The period covered is 1980-2023, twenty years before and twenty-four years after introducing market elements in national healthcare. Variables such as the number of patients discharged, consultations, doctors, and nurses are used to assess the workload level. Workload estimates are derived from a linear regression model of hospital output as the dependent variable with the number of doctors and nurses in the health system as factors. The model is tested for the stability of the regression coefficients (structural breaks) dated 2000. Results. A structural break was found in 2000 in all three dynamic rows of doctors, nurses, and discharges. There was a well-defined increasing trend in the number of patients passing through the hospitals after the liberalization of the national healthcare system. In this condition, the number of medical professionals follows its own dynamics – a slight reduction for the group of doctors and a sharp decline for the nurses in the after-reforms sub-period. These facts indicate the presence of an increasing trend in the workload and intensity of medical labour. The dependence is well established, especially in the case of nurses. Conclusions. This study confirms the hypothesis that the liberalization of the Bulgarian healthcare system, together with open-ended payment systems, caused an intensive growth of inpatient system output and workload. The expansion, especially for hospital facilities, which is not supported by a relevant number of medical professionals, threatens workplace performance and the quality of medical services.